Experimental analysis of friction during micro-forming of miniature metallic parts - Thiagaraj Devadas. (2012)
Given the detrimental impact high friction conditions have in microforming processes, interest have grown in this area in understanding how varying different characteristics during these processes could lower friction conditions. In the present study, a new die assembly was designed for a pilot friction test with improved friction sensitivity and handling capabilities. Experimentations on ETP copper samples were carried out with the new die assembly with surface roughness conditions of the dies and punches varying from 0.05Ra to 0.13Ra and with lubricants of different viscosities. Final geometries of ETP copper samples were then measured and compared against simulated friction curves. It was found that under low surface roughness condition, the impact of lubricants was insignificant and that under high surface roughness conditions, the lowest friction coefficient was recorded and introduction of lubricants was found to increase the friction coefficient.